MAQASHID AL-SYARI’AH CONCEPT OF KAFA’AH IN MARRIAGE - Barkah, Qodariyah; Andriyani, Andriyani (Universitas Islam Negeri Raden Fatah Palembang, 2020)
Basically, kafa'ah in a marriage is equality, compatibility or proportionality between the prospective bridegroom and bride. Kafa'ah in terms of religion is a necessity for a Muslim who is going to get married. One of the important things that must be done before marriage is considering several things such as nasab, religion, belief, profession, freedom, and property. However, nowadays, many couples do not heed the Kafa'ah criteria,and even many marriages happen between men and women with significant age difference. For example, a marriage between an old woman and a very young man, or vice versa. Considering these phenomena in the society, then the concept of maqasid al-shari'ah or the purpose of Islamic law is an important discussion to look at the marriage practices in the society. This is very much related to the protection of religion, soul, mind, descendant and wealth. This study analyzedlarge age disparity marriage practicesin Karang Endah village, by using the concept of ushul fiqh. The type of qualitative research used was ethnography. Research data were obtained through the use of some references such as books, journals, articles relating to the object under study. The results of this study indicated that a large age gap marriageoccurred in Karang Endah village wasbased on emotional factors of the couple. In Islam, this kind of marriage does not contradict the syari'ah rules, because Islam does not explicitly explain the age limit to be categorized as an adult. Therefore, referring to the concept of maqashid al-syari'ah, it could be concluded that large age disparity marriage occurred in Karang Endah village was carried out to protect religion, lives, and offspring of the couples. Keywords: Marriage, Kafa'ah, Age Disparity, Maqasid al-Syari'ah